Importation and distribution of unregistered medicines in the public sector: similarities, differences, and shared challenges among Southern African Development Community (SADC) countries - Admire Nyika; Bernard Ngara; Isaac Mutingwende; Luther Gwaza (BMC, 2022)
Abstract Background The purpose of the study was to assess the requirements for approval of the importation of unregistered medicines for use in the public sector in the Southern African Development Community (SADC) countries. Methods The study reviewed the legal provisions and requirements to be fulfilled when importing unregistered medicines for the public sector in SADC countries relative to two comparators drawn from countries with stringent regulatory systems through extant document analysis. The relative implementation index score was calculated and used to measure the level of implementing legal provisions and requirements to be fulfilled. Analysis was performed using the STATA software package. Results Approximately 13 out of 16 SADC countries had a relative implementation index below 50%. The aggregated implementation index across all SADC countries was 44%, ranging from 4 to 54%, while the two comparators had a relative implementation index of 81% and 85%, respectively. Conclusion Implementing the minimum requirements for importing unregistered medicines for the public sector was deficient compared to the jurisdictions with stringent regulatory systems, and wide implementation gaps also existed within the SADC region.